INTRODUCING NUMBERS TO EARLY AGE CHILDREN THROUGH SHUTTING THE KINDS OF PICTURE TYPES - M. Jamil, Ibrahim; Zulfa, Zulfa (STKIP An-Nur, 2019)
Integrated mathematics learning that can be used to develop thinking skill encourages children to develop a variety of children's intellectual potential. But there are various media that can be used in mathematics learning including real media that can be manipulated such as blocks, tangram, lego, and also abstract media like calculators, computers and so on. The research objectives here are to determine the ability in introducing numbers in early childhood through the way of drawing patterns. The approach used in this study is a qualitative approach. While the type of research used in this study is the type of classroom action research. The results of the study based on the implementation of the initial cycle can be classified in to low category, where the skills to reach (58.0%), while the ability to recognize numbers (10.0%). Based on the implementation of the first cycle cucumber skills reached (78.0%), while the ability to recognize numbers (26.0%). According to the implementation of cycle II, the ability to reach is 88.0%, while the ability to recognize numbers (44.0%). The results of the study can be concluded that the game of shutting kinds of pictures on a pillow can help students to recognize numbers quickly. Â Keywords: Numbers, Coughing, Pictures, PAUD